Performance of the CMS hadron calorimeter with cosmic ray muons and LHC beam data - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Adam, W; Arnold, B; Bergauer, H; Bergauer, T; Dragicevic, M; Eichberger, M; Erö, J; Friedl, M; Frühwirth, R; et al. (2010)
The CMS Hadron Calorimeter in the barrel, endcap and forward regions is fully commissioned. Cosmic ray data were taken with and without magnetic field at the surface hall and after installation in the experimental hall, hundred meters underground. Various measurements were also performed during the few days of beam in the LHC in September 2008. Calibration parameters were extracted, and the energy response of the HCAL determined from test beam data has been checked. © 2010 IOP Publishing Ltd and SISSA.